CULINARY SME PERFORMANCE: MARKETING CAPABILITY, ENTREPRENEURIAL ORIENTATION, COMPETITIVE ADVANTAGE AND PRODUCT INNOVATION - Ika Yuliana; Restu Alpiansah; Aryan Agus Pratama (JURNAL ILMIAH EDUNOMIKA, 2024)
Small and medium enterprises need to prepare remarkable anticipations for business continuity, one of which can develop strategic choices in the field of marketing management through entrepreneurial orientation, and develop product innovation, marketing capabilities, and competitive advantages so that it will be able to improve business performance. The population in this study is owners or managers of small and medium culinary businesses in Mataram City, with 146 respondents. Data processing methodology using Structural Equation Modeling or SEM using AMOS program. This research uses the basic theory of Service Dominant Logic (SDL). The hypothesis in this study is overall accepted except for the fifth hypothesis. Entrepreneurial orientation has a significant effect on product innovation, and marketing capability, and product innovation has a significant effect on competitive advantage; product innovation has a significant effect on SMEs’ Performance. Competitive advantage does not have a significant effect on SMEs' Performance. Competitive advantage mediates the relationship between product innovation to SMEs' performance, and product innovation mediates entrepreneurial orientation to SMEs’ performance. Keywords: SMEs’ performance, competitive advantage, entrepreneurial orientation, product innovation, marketing capability